Surfer's myelopathy: A rare presentation in a teenage gymnast and review of the literature. (April 2018) - Dillen, William L.; Hendricks, Benjamin K.; Mannas, Jonathan P.; Wheeler, Greg R.
Highlights: A review of the literature pertaining to Surfer's Myelopathy. Presentation of the first reported case of Surfer's Myelopathy in a gymnast. Delayed radiographic findings of injury sustained. Abstract: This article describes a novel setting for a rare nontraumatic spinal cord injury referred to as Surfer's myelopathy. The patient is a 16 year-old female cheerleader who presented following a gymnastics practice where she was repeatedly performing back handsprings. She demonstrated progressively worsening midthoracic back pain and evolving paraplegia and hypesthesia of the lower extremities. Magnetic resonance imaging findings were consistent with T5-T7 spinal cord ischemia at 8 h and 16 h after symptom onset. The clinical and radiologic findings for this patient are consistent with previous case reports of Surfer's myelopathy. The authors also provide a summary of the current literature describing Surfer's myelopathy, which to date includes 64 reported cases. The diagnosis of nontraumatic spinal cord injury, referred to as Surfer's myelopathy, in a gymnast highlights the importance of greater physician and patient awareness of this rare condition.